Analysis of Winds Affecting Air Pollutant Transport at La Plata, Argentina - Ratto, Gustavo (2012)
An hourly wind analysis for the populated area of La Plata city (with high industrial, power station and vehicular activi-ties) is presented and discussed. Euclidean distance and minimum covariance determinant (a robust correlation coeffi-cient) are employed, as similarity approaches, in order to compare observed wind direction frequency patterns at two monitoring sites during 1998-2003. A preliminary assessment of two sectors, namely Sector 1 (NNW-N-NNE-NE) and Sector 2 (ENE-E-ESE), relevant for the transport of industrial air pollutants towards population exposed, is discussed taking variances into account and employing a locally weighted smoothing approach (LOESS). Both similarity ap-proaches allowed gain insight of wind patterns. The distance approach showed good similarity between sites while the correlation approach showed an uneven picture depending on the wind direction. Most of the differences are explained in terms of the sea-land breeze effect but also differences in terrain roughness and data quality are taken into account. Winds from sectors 1 or 2 (analyzed during 1998-2009) may occur more than 50% of the time, most of the differences regarding the influence of the day and the season on these sectors are attributable to sea-land breeze phenomena. The LOESS proved to be appropriate to analyze the stability with time of both sectors and to discard possible remaining patterns; results are in accordance with studies that assess the interannual variability for different variables in La Plata river area. The robust correlation coefficient revealed, as an example, the linear character of dependence between winds from sector 2 and sulfur dioxide concentrations. Wind velocities and calms are also discussed.